x(x-4)(x+11)=0

Simple and best practice solution for x(x-4)(x+11)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-4)(x+11)=0 equation:


Simplifying
x(x + -4)(x + 11) = 0

Reorder the terms:
x(-4 + x)(x + 11) = 0

Reorder the terms:
x(-4 + x)(11 + x) = 0

Multiply (-4 + x) * (11 + x)
x(-4(11 + x) + x(11 + x)) = 0
x((11 * -4 + x * -4) + x(11 + x)) = 0
x((-44 + -4x) + x(11 + x)) = 0
x(-44 + -4x + (11 * x + x * x)) = 0
x(-44 + -4x + (11x + x2)) = 0

Combine like terms: -4x + 11x = 7x
x(-44 + 7x + x2) = 0
(-44 * x + 7x * x + x2 * x) = 0
(-44x + 7x2 + x3) = 0

Solving
-44x + 7x2 + x3 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-44 + 7x + x2) = 0

Factor a trinomial.
x((-11 + -1x)(4 + -1x)) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-11 + -1x)' equal to zero and attempt to solve: Simplifying -11 + -1x = 0 Solving -11 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -1x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = 0 + 11 -1x = 0 + 11 Combine like terms: 0 + 11 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11

Subproblem 3

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {0, -11, 4}

See similar equations:

| 4d*-3d= | | (28-4i)-(10-30)=0 | | 3+8x=14-3x | | 1-4(100+36s)=15-4s | | y^2-4y=8 | | 8x+8-ax-a=0 | | 3(x-3)=2(x-2)-(5-3x) | | 0.50(8n-2)=16-30n | | 2x^2+10x-80=0 | | x(2x+3)(x-4)=6 | | x(2x+5)(x-4)=6 | | 9m+5-4m=-20 | | 13x-30=7x-14 | | -6(x-3)=-3(x+9) | | (x-p)(x^2+11x+15)=(x^2-9)(2x+q) | | 2x^2-3-15=0 | | k+84738398=98393398 | | 8+9t=21t-17 | | X^2+.52x=-25 | | 3(b+4b)=40-15+20 | | -4(w-3)-6w=-2(w+6) | | 0=0.4t^2-7.7t+0.5 | | 0.2+10000= | | 3+9*2= | | 2(x-6)+3(2-3x)=5(2x-1)+4x-1 | | 3c+5=4 | | F(x)=x^2-4+6 | | 5(19m-18)=-8-7(-15m-14) | | (2x)3=8 | | 5x^2y+15y-35=0 | | x^5-2x^4=0 | | X*5*0.0333+X=120 |

Equations solver categories